Radiologic and computed tomography evaluation of the beaks from three bird species - da Silva, Daniel Simões [UNESP]; Rahal, Sheila Canevese [UNESP]; da Silva, Jeana Pereira [UNESP]; Mamprim, Maria Jaqueline [UNESP]; de Camargo, Gabriel Corrêa [UNESP]; Cassanego, Guilherme Rech [UNESP]; Ichikawa, Ricardo Shoiti [UNESP] (Wiley, 2024)
This study aimed to evaluate the beaks of three species of birds using radiography and computed tomography (CT). The mean lengths of maxillary and mandibular rostra on radiographs were highest for toco toucan, followed by buff-necked ibis, and least for red-legged seriema birds. The height and width of maxillary and mandibular rostra measured on CT had mean values highest for toco toucans, followed by red-legged seriema, and least for buff-necked ibis. Except for the proximal region of the maxillary rostrum, the HU values were positive for other regions of the maxillary and mandibular rostra in the buff-necked ibis and red-legged seriema and negative in all for the toco toucan.
Keywords: avian; imaging study; measurements; Neotropical birds